Prototype Development of Social Personal Guidance Guide using Role-Playing Techniques to Improve Social Interaction of Children with Intellectual Requirements - Sartinah, Endang Pudjiastuti; Andajani, Sri Joeda; Pamuji, Pamuji (Journal of ICSAR, 2023)
This manual aims to make it easier for teachers to deal with the problems of mentally disabled children in terms of social interaction. The development of the teacher's manual uses the 4-D model of Thiagarajan, S, Semmeln, D, S & Semmel MI (1974) which has been modified with the following stages: define, design, and develop. Data collection techniques are used in assessment instruments to obtain validation data, observations to obtain data on children's abilities during learning activities, and teacher responses to the personal social tutoring teacher manual with role-playing techniques. Data analysis used quantitative description. The results showed that using the teacher's manual in personal social guidance with role-playing techniques increased the social interaction of mentally disabled children. After giving ten times treatments to mentally disabled children, the social interaction of mentally disabled children increased. Mentally disabled children were able to interact with their friends step by step. Step independently. This can be seen from the results of the practical value of the teacher's manual is 2.7, and the value of the effectiveness of the teacher's manual is 3.0. So we can conclude that using the teacher's manual in personal social guidance with role-playing techniques to increase the social interaction of mentally disabled children in inclusive elementary schools is feasible.